2013
DOI: 10.5194/cp-9-657-2013
|View full text |Cite
|
Sign up to set email alerts
|

HadISDH: an updateable land surface specific humidity product for climate monitoring

Abstract: HadISDH is a near-global land surface specific humidity monitoring product providing monthly means from 1973 onwards over large-scale grids. Presented herein to 2012, annual updates are anticipated. HadISDH is an update to the land component of HadCRUH, utilising the global high-resolution land surface station product HadISD as a basis. HadISD, in turn, uses an updated version of NOAA's Integrated Surface Database. Intensive automated quality control has been undertaken at the individual observation level, as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 44 publications
(50 reference statements)
0
52
0
1
Order By: Relevance
“…Since the 1970s, when most humidity monitoring records begin, until the turn of the century, specific humidity has increased over most of the well-observed parts of the globe (Dai, 2006;Berry and Kent, 2011;Willett et al, 2013). This has been largely driven by rising surface temperatures, which have, in turn, increased the water holding capacity of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, when most humidity monitoring records begin, until the turn of the century, specific humidity has increased over most of the well-observed parts of the globe (Dai, 2006;Berry and Kent, 2011;Willett et al, 2013). This has been largely driven by rising surface temperatures, which have, in turn, increased the water holding capacity of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…PHA has been used on NCDC's US Historical Climatology Network (USHCN) monthly surface temperature record, and subsequently applied to the Global Historical Climatology Network (GHCN) (Lawrimore et al, 2011) and more recently to surface humidity measurements (Willett et al, 2013(Willett et al, , 2014. PHA has been designed to run on large networks of stations in an automated fashion, and hence suits the requirements of homogenising HadISD.…”
Section: Homogenisation On Monthly Scalesmentioning
confidence: 99%
“…HadISD is updated on an annual basis, with each new release being given a unique version number to allow full traceability, with the current version (v1.0.2.2013f) running to the end of 2013. HadISD is an updated, quality-controlled data set, but it has not as yet been homogenised, although it the basis of the monthly homogeneous specific humidity product (Willett et al, 2013). Initial steps in releasing a homogenised HadISD are detailed in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Willett et al (2013) reported that the maximum uncertainties in humidity measurements with dry-and wet-bulb thermometers amounted to 2.75 and 5 % RH at temperatures of 0 and −10 • C, respectively. Emeis (2010) summarized the errors for various measurement equipment: for example, advanced equipment based on the capacitive method has an accuracy of 2 % RH (for a humidity of 10-80 % RH) to 3 % RH (for a humidity of 80-ca.…”
Section: Sensitivity Experiments With Hypothetical Bias In Humiditymentioning
confidence: 99%
“…Haddeland et al (2012) intensively examined the compound effects of the bias correction of radiation, wind and humidity, and showed that bias correction has an impact on absolute values of evapotranspiration but less impact on relative changes. Moreover, global humidity observation data sets contain uncertainties originating from the accuracy of measurements, grid sampling (Willett et al, 2013) and the spatial variability within land cells. Knowing the sensitivity of irrigation water to humidity conditions at different locations would help clarify the Table 1.…”
Section: Introductionmentioning
confidence: 99%